Youth, religion, and identity in a globalizing context: international perspectives - Gareau, Paul L.; Bullivant, Spencer Culham; Beyer, Peter (Youth in a globalizing world, 2019)
Front Matter -- Copyright Page -- Acknowledgement -- Illustrations -- Notes on Contributors -- Introduction: Youth, Religion and Identity in a Globalizing Context: Canadian, Australian, American, and German Case Studies /Paul L. Gareau , Spencer Culham Bullivant and Peter Beyer -- Religion, Spirituality, and Nonreligion -- Religious Identity Construction among Young Adults in Canada: the Religious, the Spiritual, and the Non-Religious /Peter Beyer , Scott Craig and Alyshea Cummins -- So You Think You Are Religious, or Spiritual but Not Religious: So What? /Reginald Bibby -- Influences of Religion on the Sexual Attitudes and Practices of Canadian Youth: the Case of Premarital Sex /Pamela Dickey Young -- Not Your Daddy’s Atheism: Understanding Generational Differences between Non-Religious Americans /Spencer Culham Bullivant -- Minorities, Diversity, and Recognition -- Gender and Marriage among Religious Youth in Quebec: Sexual Ethics as a Source of Distinction /Géraldine Mossière and Josiane Le Gall -- “I Am a Normal Girl”: Shi’i Muslim Young Girls’ Social Worlds within Canada and Abroad /May Al-Fartousi -- Beyond the Congregation: Evangelical Conferencing and Religious Adherence among Chinese-Canadian Youth /Scott Wall -- Socio-Economically Disadvantaged Youths in Germany and Religious Diversity in Daily Life /Dörthe Vieregge -- Agency, Ambivalence, and Adaptation -- Apathy or Misunderstanding?: Youth’s Reflections on Their Religious Identity in Canada /Heather Shipley -- Exploring the Worldviews of Quebec Adolescents: Results from a Qualitative Study /Marie-Paule Martel-Reny -- Striking a Path through the Wilderness: the Negotiations of Catholic Evangelical Youth in a Secular and Diverse Canada /Paul L. Gareau -- “Whatever”? Religion, Youth, and Identity in 21st Century Australia /Anna Halafoff and Laura Gobey -- Conclusion: Youth, Religion and Identity in a Globalizing Context: International Case Studies /Peter Beyer.